Adoption of Electronic Cash Payment among Students: A Case Study of Siem Reap Build Bright University - POR, Narith; SAY, Chanminea; MOV, Socheat (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
This research aimed to assess students' awareness and adoption of electronic cash and analyze the factors influencing their attitudes towards this payment method. The study was conducted in Siem Reap province, Cambodia, with 211 students from Build Bright University. Findings indicated that the majority of respondents had knowledge and understanding of electronic cash, highlighting a positive level of familiarity. Convenience and ease of use influenced students' adoption of electronic cash. Students valued the seamless experience, quick transactions offered by electronic cash, and prioritizing security and privacy. Technological appeal and innovation also played a crucial role in shaping students' preferences. Trust in the payment system and perceived benefits such as rewards and discounts were influential factors.